Phytotoxicity of Fusarium, other fungal isolates, and of the phytotoxins fumonisin, fusaric acid, and moniliformin to jimsonweed - Abbas, H.K.; Boyette, C.D.; Hoagland, R.E. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
Ten fungal isolates from jimsonweed (Datura stramonium L.) and 7 from crop species were examined for phytotoxin production and pathogenicity on jimsonweed seedlings in the greenhouse. Four isolates of Fusarium moniliforme, three F. semitectum isolates, a F. oxysporum isolate, a Cephalosporium spp. isolate, and an Alternaria crassa isolate from diseased jimsonweed seedlings, plus seven additional F. moniliforme isolates from seeds and seedlings of crop species were grown on autoclaved rice (Oryza sativa). The fungus-rice mixtures were ground and tested for phytotoxicity on 1- and 2-wk-old jimsonweed seedlings via foliar application. All fungus-infested rice extracts (5 g fungus-rice mixture 50 mL-1 water) caused injury or mortality to the seedlings except the extracts from isolates of F. semitectum, Cephalosporium spp., and A. crassa. Fungus-rice mixtures were quantitatively analyzed for the presence of Fusarium phytotoxins [fumonisin B1 (FB1 fusaric acid, and moniliformin]. No isolate produced more thanoneof these phytotoxins in the fungus-rice extract. FB1 was produced by ail F. moniliforme isoletes in a concentration range of ≤ 5 to 850 μg mL-1 of fungus-rice extract. The F. oxysporum isolate produced moniliformin at 3.5 g mL-1, and no phytotoxins were detected in extracts of F. semitectum, Cephalosporium spp., or A. crassa. Pure fumonisin, fusaric acid, and moniliformin applied to jimsonweed foliage at 6-50, 25-800, and 50-800 (μg mL-1, respectively, caused symptoms similar to that of the fungal isolates that produced these compounds. Pathogenicity tests of spores of all isolates on jimsonweed indicated that the isolates were avirulent, except for A crassa which infected only after a dew period ≥ 12 h.